Analysis of Acoustic Surface Wave Focused Unidirectional Interdigital Transducers Using Coupling-of-Mode Theory - Guopeng Hui; Tinglun Ao; Haotian Liu; Minglei Li; Chen Chen (Micromachines)
In cell or droplet separation, high acoustic wave energy of a surface acoustic wave (SAW) device is required to generate sufficient acoustic radiation force. In this paper, the electrode width-control floating electrode focused unidirectional interdigital transducer (EWC-FEFUDT) is proposed due to its enhanced focusing properties. The performance of the EWC-FEFUDT is investigated using the Coupling-of-Mode (COM) theory, and the COM parameter is extracted using the Finite Element Method (FEM). The four different forbidden band edge frequencies account for the unidirectionality of the proposed EWC-FEFUDT. A direction angle of <semantics>ϕκ−ϕζ=44.5°</semantics> of the EWC-FEFUDT (Design 3) is obtained, being fairly close to the optimum value of 45°. The EWC-FEFUDT (Design 3) has a lower insertion loss (IL) of −5.1 dB and greater unidirectionality (20 × log10(<semantics>D</semantics>) = 13.8 dB). The SAW maximum amplitude of the EWC-FEFUDT (Design 3) is increased by about <semantics>1.5×10−4 µm</semantics> compared to that of the focused interdigital transducers (FIDTs). The maximum acoustic pressure of the EWC-FEFUDT is an order of magnitude higher than that of FIDTs. The EWC-FEFUDT exhibits enhanced focusing properties. The proposed EWC-FEFUDT may provide an alternative method for cell or droplet separation in an efficient manner.